AN ANALYSIS OF CODE MIXING USED IN THE COMMERCIAL ADVERTISEMENTS ON THE NEWSPAPER AND ITS INFLUENCES TOWARD THE DEVELOPMENT OF LANGUAGE LEARNING - Rini Mulyani (Journal of English Education Program (JEEP), 2018)
This  study  is  aimed  at  investigating  the  types  of  code  mixing  used  in  the commercial advertisement in the  newspaper and the influence of the used of code mixing in commercial advertisement appear toward the development of language learning.   The   study  used   descriptive   study  for  retaining   the   holistic   and meaningful characteristic of real life event. The population was all the commercial advertisements   on   several   newspapers   which   consist   of   30   commercial advertisement  and  took fifteen  commercial  advertisements  as the  sample.  The instruments  used  to  collect  the  data  were  newspaper  advertisements  by using content analysis as the technique to analyze the data and questionnaire used to get the influence the code mixing toward the language learning. Actually, the result showed that code mixing is one of a number of the linguistic manifestations  of language contact and mixing. It shows that there were three types of code mixing; situational switching, metaphorical switching, and conversational switching. Accordingly, there were some kind of code mixing including emblematic, intra- sentential, inter-sentential, and intra-lexical code mixing. In conclusion,  the most types of code  mixing  used  in the  newspaper  was inter-sentential  code  mixing which the percentage 86%, and intra-sentential as the second findings which the percentage was 13%, and the last emblematic which  the percentage was 1%. In addition, the suggestion of this study was aimed at investigating  the application  of code mixing in education  field  and also  the other researcher to repair the study more perfect.